Growth curve pea in different seasons as a function of accumulated thermal sum - Tartaglia, Francieli de Lima; Dal'Col Lúcio, Alessandro; Inês Diel, Maria; Lambrecht, Darlei Michalski; Luís Tischler, André; Sgarbossa, Jaqueline (Comunicata Scientiae, 2023)
The objective of this study was to determine the performance of peas grown in the field, in three growing seasons, by adjusting the nonlinear logistic model and its critical points. Uniformity trials were conducted in the field in the years 2016, 2017 and 2018 in the experimental area of the Crop Science Department of the Federal University of Santa Maria. The cultivar used was the Pea Grain 40. The values of the average mass of pods per plant, obtained in each harvest, were accumulated successively for each row of cultivation. After adjusting the nonlinear logistic model, the average pod mass per plant as a function of the accumulated thermal sum and the critical points were estimated by the partial derivatives of the adjusted function. The adjustment of the parameters of the logistic model and the critical points calculated by bootstrap resampling allowed comparisons to be made between the times of pea cultivation. The pea crop is influenced by environmental conditions, which interferes with the crop cycle and productivity. Season 1 was the most productive, with maximum increases in production in the shortest period (592.5 °C days-1 to produce 119.52 g plant-1), causing a high production peak in relation to the other seasons analyzed. The adjustment of the logistic model allowed to describe the pea production cycle over time at different growing seasons.